2005
DOI: 10.1002/smj.484
|View full text |Cite
|
Sign up to set email alerts
|

Embedded ties and the acquisition of competitive capabilities

Abstract: We build on previous research that explores the external acquisition of competitive capabilities through the embedded ties that firms form in networks and alliances. While information sharing and trust have been theorized to be key features of the interorganizational ties that facilitate the acquisition of competitive capabilities, we argue that these mechanisms provide an incomplete explanation because they do not fully address the partially tacit nature of the knowledge that underlies competitive capabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
595
2
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 687 publications
(625 citation statements)
references
References 78 publications
16
595
2
12
Order By: Relevance
“…Consequently, the chance of achieving differentiation competitive advantage through this group is limited. Conversely, joint problem solving with suppliers is more common, varies to a greater extent and, therefore, is more consequential in terms of achieving cost competitive advantage (McEvily and Marcus, 2005) through a better product quality and improved product features, or through a reduction of production costs (e.g. through packaging reductions or material substitution) and related processes, which can generate material savings or convert waste into valuable forms (Porter and Van der Linde, 1995).…”
Section: Discussion and Managerial Implicationsmentioning
confidence: 99%
“…Consequently, the chance of achieving differentiation competitive advantage through this group is limited. Conversely, joint problem solving with suppliers is more common, varies to a greater extent and, therefore, is more consequential in terms of achieving cost competitive advantage (McEvily and Marcus, 2005) through a better product quality and improved product features, or through a reduction of production costs (e.g. through packaging reductions or material substitution) and related processes, which can generate material savings or convert waste into valuable forms (Porter and Van der Linde, 1995).…”
Section: Discussion and Managerial Implicationsmentioning
confidence: 99%
“…Relational mechanisms, defined as partners' behaviors and interactions over the course of the alliance, capture the conditions that allow organizations to work collaboratively in spite of their organizational differences (Kale and Singh 2007;Kale et al 2000;Lavie et al 2012). Prior work has suggested that relational mechanisms play an important role in alliance success (e.g., Lavie et al 2012;McEvily and Marcus 2005). We distinguish three types of relational mechanisms-mutual trust, relational embeddedness, and relational commitment.…”
Section: Mediating Role Of Relational Mechanismsmentioning
confidence: 99%
“…We differentiate three types of relational mechanismsmutual trust, relational embeddedness, and relational commitment (Lavie et al 2012). Although existing literature suggests the strong association between relational mechanisms and alliance management (e.g., Dyer and Singh 1998;McEvily and Marcus 2005), the issue of the roles that various relational mechanisms play in the alliance management routines-alliance performance relationship remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Converse to alliances, contact networks consist of non-formalised interaction and relationships between organisations. The structure of these networks is often more dynamic, as organisations continually update and change their contacts (Burt 1992;Huggins 2000Huggins , 2001McEvily and Marcus 2005;Grabher and Ibert 2006;Trippl et al, 2009). Contact networks can be considered to be a particular form, or subset, of the type of wider contact systems facilitating the flow of resources and economic development within and across regions (Thorngren, 1970;Malecki, 1989;Anselmo de Castro and Jensen-Butler, 2003).…”
Section: Inter-organisational Network and Knowledge Flowmentioning
confidence: 99%